1999
DOI: 10.3354/ame019285
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical transformations and potential polyaromatic hydrocarbon degradation in macrofaunal burrow sediments

Abstract: ABSTRACT-A variety of polyaromatic hydrocarbons (PAH) includmg naphthalene, phenanthrene, acenaphthene, and dibenzothiophene were degraded with little or no lag in oxic slurries of marine sedi m e n t~ from burrow walls constructed by benthic macrofauna. PAH degradation potentials of burrow sediments from the polychaetes Nereis virens and Clymenella torquata, the mollusc Mya arenaria and the enteropneust Saccoglossus bromophenolosus were generally greater than potentials for non-burrow sedirnents; relative rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…2). These results are consistent with the established view of microbial PAH degradation being highly favored by the presence of molecular oxygen (Cerniglia & Heitkamp 1989), and also with results from Chung & King (1999) and Coates et al (1996) who found no correlation between PAH mineralization and the availability of other electron acceptors such as nitrate, sulfate and ferric iron in moderately polluted field-collected sediment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…2). These results are consistent with the established view of microbial PAH degradation being highly favored by the presence of molecular oxygen (Cerniglia & Heitkamp 1989), and also with results from Chung & King (1999) and Coates et al (1996) who found no correlation between PAH mineralization and the availability of other electron acceptors such as nitrate, sulfate and ferric iron in moderately polluted field-collected sediment.…”
Section: Discussionsupporting
confidence: 81%
“…The intensity of the macrofaunal impact on biogeochemical processes has, however, been shown to be highly species-specific and particularly attributed to differences in macrofaunal behavior (Aller & Yingst 1985, Andersen & Kristensen 1991. Since most studies apply whole sediment or 2-compartment models when studying contaminant fate, the relative importance of macrofaunal burrows, compared to surface and bulk sediments, for the microbial degradation of PAHs and other contaminants in marine sediment is yet highly unexplored with, to our knowledge, only 2 published studies (Chung & King 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Burrows may, thus, be considered extensions of the oxic surface layer with respect to pyrene degradation. These observations are in accordance with Chung & King (1999) and Granberg et al (2005), who also found that mineralization rates in burrow sediments were much higher than in the surrounding sediment, and in a few cases even higher than mineralization rates in surface sediment. Aerobic bacteria able to grow solely on pyrene were found in burrow sediment from both polychaetes at the same or slightly higher abundances than in surface sediments (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The similarities in pyrene degradation between burrow and surface sediments suggest that the oscillating oxygen concentration in ventilated burrows is sufficient to maintain a PAH-degrading capacity similar to the sediment surface with more constant oxygen concentrations. Since PAH degradation rates seem to depend on oxygen exposure time (Chung & King 1999), the actual in situ mineralization rates are probably lower in burrows compared with surface sediments because oxygen is not always present in the burrow (Timmermann et al 2006). Given the high potential for PAH mineralization in the burrows, we expect pyrene degradation to occur whenever oxygen is provided by ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation